2017
DOI: 10.3329/bjch.v41i1.33635
|View full text |Cite
|
Sign up to set email alerts
|

Noninherited Risk Factors of Congenital Heart Defects in Offspring: A Revi

Abstract: Prognosis of children with congenital heart defects (CHDs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…CHDs are highly prevalent problems with mostly unknown origins. One study found that multiple environmental exposures for pregnant women, including living in newly renovated rooms, living in homes near major traffic, smoking, and having a manual labor occupation, were significantly associated with CHDs in their offspring (Mamun et al 2017 ). As shown in our study, both maternal living/working environment exposure and occupational exposure are risk factors for CHDs in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…CHDs are highly prevalent problems with mostly unknown origins. One study found that multiple environmental exposures for pregnant women, including living in newly renovated rooms, living in homes near major traffic, smoking, and having a manual labor occupation, were significantly associated with CHDs in their offspring (Mamun et al 2017 ). As shown in our study, both maternal living/working environment exposure and occupational exposure are risk factors for CHDs in offspring.…”
Section: Discussionmentioning
confidence: 99%